The future of Eastern European capital markets - Jens Köke; Michael Schröder (EIB Papers, 2002)
Capital markets are - by definition - a fairly new phenomenon for countries that started embracing capitalism a little more than ten years ago. More specifically, the first securities exchanges in Central and Eastern Europe (CEE) opened at the beginning of the 1990s and the last had been set up by the mid-1990s. Given their short history, it is not surprising that CEE capital markets continue to be relatively small. What is more, the global market downturn over the last one and a half years has not left CEE capital markets unscathed. Against this background, this paper examines the status of CEE capital markets - including their contribution to the financing corporate investment - and discusses strategies to advance their development.
Keywords: 330; Finanzmarkt; EU-Erweiterung; Osteuropa